Networked Care: Worlding Mental Well‐Being in a Digital Age - Kolehmainen, Marjo (Wiley, 2025)
This article analyses mental health support through the lens of care. Drawing upon a study of various practices of teletherapy and remote counselling during the COVID-19 pandemic, it empirically analyses mental healthcare by tapping into the experiences of Finnish therapy and counselling professionals. In telecare, digital technology with its particularities brings forth particular forms of (networked) care: networked connectivity and the relations formed with and through digital technologies operate as ‘worlding practices’ that bring different modes of mental healthcare into being. Taking as its point of departure the assumption that networked connectivity has transformed and is transforming mental healthcare, this article seeks ways of incorporating networked connectivity into understandings of the enactment of care. By bringing together insights from science and technology studies, feminist materialism and research on networked connectivity, it is interested in asking and analysing how care comes to matter in networked societies. In particular, insights from studies of care networks and network connectivity are brought together to provide novel insights into these configurations and entanglements of care. Through detailed empirical analysis of interviews, the article further develops a concept of networked care.